The effects of pH on the morphology and structural properties of Er/Yb co-doped hydroxyapatite - Mohammed, Bast Ahmed; Ateş, Tankut; Mahmood, Bahroz Kareem; Kareem, Rebaz Obaıd; Keser, Serhat; Bulut, Niyazi; Kaygılı, Omer (Niyazi BULUT, 2024)
The present study includes a detailed investigation of the effects of various pH conditions used in the synthesis on the structural properties of hydroxyapatite (HAp) co-doped with Er and Yb at a constant value. In this context, we changed the pH value from 8.5 to 11.0 with the steps of 0.5 in the synthesis. It was seen that the different pH causes significant variations in the crystallite size, lattice parameters, unit cell volume, and morphology. The pH value plays a key role in the synthesis of Er/Yb co-doped HAps.
Keywords: Materials Engineering (Other); Malzeme Mühendisliği (Diğer)